2015
DOI: 10.1001/jama.2015.13971
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Diagnosed Pertussis Infection in Children and Long-term Risk of Epilepsy

Abstract: In Denmark, risk of epilepsy was increased in children with hospital-diagnosed pertussis infections compared with the general population; however, the absolute risk was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Long term follow-up data do not suggest an increased asthma risk in adulthood 525354. Small studies have suggested possible intellectual impairment55 and slight increased risk of developing epilepsy56 after childhood pertussis, but these studies are underpowered and lack long term follow-up.…”
Section: What Are the Risks?mentioning
confidence: 99%
“…Long term follow-up data do not suggest an increased asthma risk in adulthood 525354. Small studies have suggested possible intellectual impairment55 and slight increased risk of developing epilepsy56 after childhood pertussis, but these studies are underpowered and lack long term follow-up.…”
Section: What Are the Risks?mentioning
confidence: 99%
“…It is important to note that although apneic episodes are frightening, they do not cause death. However, the hypoxia associated with an apneic episode may be a causative factor in later epilepsy and subsequent intellectual impairment [16, 17]. …”
Section: Clinical Characterisitcs Of Bordetella Pertussis Infection Imentioning
confidence: 99%
“…Few studies have looked into the association between a wide range of infections and the subsequent risk of epilepsy, but a number of studies have examined the risk of epilepsy after specific infections. A previous Danish register–based study looking specifically at Bordetella pertussis infections found a subsequent HR for epilepsy of 1.7 (95% CI 1.3‐2.2), with higher risk for those with a longer duration of admission for infection and a similarly increased risk across different age groups of infections . The risk of epilepsy after toxoplasmosis was systematically reviewed in an article from 2015, which reported a pooled odds ratio for epilepsy of 2.25 (95% CI 1.27‐3.98) .…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Immunologic hypotheses about subgroups of epilepsy have gained growing attention in recent years, with several studies suggesting a connection between infections and the development of epilepsy. [4][5][6][7][8] Infection of the central nervous system (CNS), in particular, is a well-known risk factor for epilepsy and is considered "the main cause of seizures and acquired epilepsy in the developing world." 4 However, infections outside of the CNS can also harm the brain, for example, through induction of inflammatory responses affecting the brain, including the development of autoantibodies that can cross-react with brain antigens.…”
Section: Introductionmentioning
confidence: 99%